MQTT-BASED IOTS NETWORK PERFORMANCE ANALYSIS - Albin Lemuel Kushan; Azmi Aminordin; Shahadan Saad; Adib Farhan Azzemi; Muhammad Syahid Farhan Mohd Jeman; Ahmad Firdaus Ahmad Fadzil (Journal of Islamic, Social, Economics and Development, 2021)
Recent years has seen the rise of popularity of IoT. IoT has become a hot topic discussed in many forums, blogs, and talks. Due to that, big companies, remote area industries, SOHO, and home users are thinking about implementing IoT into their daily operation. However, there are several factors that need to be analyzed before IoT can be implemented. This paper focused on the performance of MQTT-based IoT ecosystem. Packet length and response time are two of the metrics that going to be analyzed in this project using Wireshark. IoT are intended to replace a more traditional and conventional ways of performing tasks. Thus, if the performance of the IoT does not reflect any improvement over the current system, there is no point in implementing IoT into daily operation. From the experiment conducted, it is indicated that MQTT is a better protocol to be used in IoT ecosystem as compared to HTTP. The result gathered proved that MQTT are a better choice to be used by low-power devices. Result obtained in this paper can be useful to companies, industries, SOHO, and home users.